Carbon-coated nano-silver particles, preparation method thereof and conductive silver paste
The preparation of carbon-coated nanosilver particles through solid phase reaction and used for photovoltaic conductive silver paste solves the problem of using irritating compounds and long preparation time in the prior art, and achieves cost reduction and improved conductivity.
Patent Information
- Application Number
- CN202411853727.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
Tris(tetraaminophenyl)benzene or tris(tetraaminophenyl)amine compounds used in the prior art stimulate the eyes, respiratory system and skin, and are not conducive to large-scale industrial production.
Carbon-coated nanosilver particles were prepared by a simple solid phase reaction, and the organic carbon source precursor and silver-containing compounds were calcined in an inert gas to obtain carbon-coated nanosilver particles, and partially replaced silver powder for photovoltaic conductive silver paste.
The use of irritating compounds is avoided, which shortens preparation time, reduces cost, and improves the uniformity and conductivity of conductive silver paste.
Smart Images

Figure CN119724745A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a carbon-coated nano silver particle and a preparation method thereof, and a conductive silver paste. Background Art
[0002] Photovoltaic silver paste is mainly composed of three parts: conductive phase, binder phase and organic carrier. The performance of the conductive phase directly affects the bulk resistance and contact resistance of the electrode material. Silver is a metal with excellent conductivity and is generally used as the main conductive phase of photovoltaic silver paste. However, the unit price of silver is relatively high. Under the condition of ensuring conductivity, studying substitutes for silver powder has become a research hotspot in this field.
[0003] The prior art (CN201910709606.5) discloses a method for preparing a carbon-supported nanosilver catalyst, comprising mixing a compound containing an -NH2 functional group with an appropriate amount of an organic solution, stirring at room temperature until completely dissolved; then dissolving AgNO3 in an appropriate amount of an organic solvent and dropping it into the solution, stirring at room temperature for 10-15 hours, and centrifuging and vacuum drying to obtain a polymer metal complex. The metal complex is placed in a muffle furnace and an inert gas is introduced to the temperature at 4-6°C / min to 750-950°C and calcined for 1.5-3 hours to obtain a carbon-supported nanosilver catalyst.
[0004] The disadvantages of the prior art are that the tris(tetraaminophenyl)benzene or tris(tetraaminophenyl)amine compounds used can irritate the eyes, respiratory system and skin, and the carbon morphology of the product produced by a single complexation cannot be controlled, which is not conducive to multi-purpose use. In addition, the preparation time is too long, which is not conducive to large-scale industrial production. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies in the prior art, the purpose of the present invention is to provide a carbon-coated nano-silver particle and a preparation method thereof, and a conductive silver paste. The carbon-coated nano-silver particles are prepared by a simple solid-phase reaction, and the carbon-coated nano-silver particles are used to partially replace silver powder for photovoltaic conductive silver paste, which can reduce the use of silver powder and effectively reduce costs.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing carbon-coated nano-silver particles, comprising the following steps:
[0008] mixing and grinding an organic carbon source precursor and a silver-containing compound;
[0009] calcining the ground solid mixture under an inert gas atmosphere;
[0010] The calcined product is cooled, washed and dried to obtain carbon-coated nano-silver particles.
[0011] Furthermore, the silver-containing compound is silver oxide or a silver salt which is decomposed to obtain silver element during the preparation of the carbon-coated nano-silver particles.
[0012] Furthermore, the silver-containing compound is silver oxide, and the silver oxide is prepared by the following steps:
[0013] dissolving silver nitrate in deionized water to obtain a silver nitrate solution;
[0014] Then, sodium hydroxide is added dropwise to the above silver nitrate solution until it becomes alkaline, mixed evenly, and allowed to stand to obtain a precipitate;
[0015] The precipitate is centrifuged, washed and dried to obtain silver oxide.
[0016] Furthermore, the concentration of the silver nitrate solution is 1 to 2 mol·L -1 , the concentration of sodium hydroxide is 0.5~1mol·L -1 .
[0017] Furthermore, the mass ratio of the organic carbon source precursor to the silver-containing compound is (40-80):(60-100).
[0018] Furthermore, the grinding process specifically includes: placing the organic carbon source precursor and the silver-containing compound in an agate jar and ball milling for 8-12 hours.
[0019] Furthermore, the calcination process specifically includes: placing the solid mixture in a calcination device, heating it to 700-800° C. at 2-5° C. / min under an inert gas atmosphere, and maintaining it for 1-2 hours.
[0020] Furthermore, the cleaning and drying process specifically includes: washing the calcined product with water and then drying it at a temperature of 60 to 80°C.
[0021] The present invention also provides a carbon-coated nano-silver particle, which is prepared by the above-mentioned method for preparing the carbon-coated nano-silver particle.
[0022] The present invention also provides a conductive silver paste, which, based on the total weight of the conductive silver paste being 100%, comprises:
[0023] Silver powder 82-88%;
[0024] 1-7% of the carbon-coated nanosilver particles as described above;
[0025] Glass powder 1-3%;
[0026] Organic resin 4-6%;
[0027] Organic solvent 2-8%;
[0028] Thixotropic agent 0.1~0.3%;
[0029] Leveling agent 0.2~0.5%;
[0030] Dispersant 0.1~0.3%.
[0031] The beneficial effects of the present invention are:
[0032] (1) The silver-containing compound is used as a template to prepare carbon-coated nano-silver particles in one step. The carbon-coated nano-silver particles are prepared by a simple solid-phase reaction, avoiding the use of irritating and harmful compound reagents such as -NH2 compounds. At the same time, the silver-containing compound can be used as a template to control the morphology of carbon and can be heated to generate nano-silver particles. The organic carbon source precursor dissolves and wraps the nano-silver particles during the calcination process. As the temperature rises, the organic carbon source precursor is carbonized to generate carbon-coated nano-silver particles (Ag@C). The reaction conditions are mild, the preparation process is simple, the cost is low, and it is relatively easy to achieve industrial production.
[0033] (2) Carbon-coated nanosilver particles can partially replace silver powder for photovoltaic conductive silver paste, which can reduce the use of silver powder and effectively reduce costs;
[0034] (3) Carbon materials can improve the dispersibility of silver nanoparticles in the slurry and prevent particle agglomeration, thereby improving the uniformity and conductive properties of the conductive silver paste;
[0035] (4) Carbon materials have excellent electrical conductivity. Carbon-coated nanosilver particles can partially replace silver powder for photovoltaic conductive silver paste, which can further reduce the bulk resistance and improve the electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is the SEM spectrum of the carbon-coated nanosilver particles in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing carbon-coated nano-silver particles, comprising the following steps:
[0038] mixing and grinding an organic carbon source precursor and a silver-containing compound;
[0039] calcining the ground solid mixture under an inert gas atmosphere;
[0040] The calcined product is cooled, washed and dried to obtain carbon-coated nano-silver particles.
[0041] In this embodiment, the silver-containing compound is used as a template to prepare carbon-coated nano-silver particles in one step. The carbon-coated nano-silver particles are prepared by a simple solid-phase reaction, avoiding the use of irritating and harmful compound reagents such as -NH2 compounds. At the same time, the silver-containing compound can be used as a template to control the morphology of carbon and can be heated to generate nano-silver particles. The organic carbon source precursor dissolves and wraps the nano-silver particles during the calcination process. As the temperature rises, the organic carbon source precursor is carbonized to generate carbon-coated nano-silver particles (Ag@C). The reaction conditions are mild, the preparation process is simple, the cost is low, and it is relatively easy to implement. Industrial production; using carbon-coated nano-silver particles to partially replace silver powder for photovoltaic conductive silver paste can reduce the use of silver powder and effectively reduce costs; carbon materials can improve the dispersibility of silver nano-particles in the paste and prevent particle agglomeration, thereby improving the uniformity and conductivity of the conductive silver paste; carbon materials have excellent electrical conductivity, and carbon-coated nano-silver particles partially replace silver powder for photovoltaic conductive silver paste, which can further reduce bulk resistance and improve electrical conductivity; compared with other methods of reducing silver content by replacing it with organic matter, the present invention can greatly retain electrochemical properties and reduce conversion efficiency losses.
[0042] Among them, the organic carbon source precursor can be selected as polyvinyl pyrrolidone (PVP), which melts and wraps the nanosilver particles at 260°C, and can be used as a surfactant to avoid the agglomeration of the product to obtain carbon-coated nanosilver particles with uniform morphology and structure. The carbon-coated nanosilver particles are spherical in structure, which can effectively reduce the printing resistance and reduce the risk of network blocking. At the same time, the three-dimensional spherical structure can maintain the height of the printed line to avoid line collapse and current loss; and the carbon nanospheres have excellent electrical conductivity, which has little effect on electrical properties when used in photovoltaic conductive silver paste.
[0043] Furthermore, the silver-containing compound is silver oxide or a silver salt that is decomposed to obtain silver element during the preparation of carbon-coated nano-silver particles. Among them, silver oxide can be decomposed into nano-silver particles during heating, and silver oxide is preferred because it produces few by-products (only oxygen) during heating and is easy to decompose; the silver salt can be selected from silver nitrate, silver sulfate, and silver halide.
[0044] Further, the silver-containing compound is silver oxide, and the silver oxide is prepared by the following steps:
[0045] dissolving silver nitrate in deionized water to obtain a silver nitrate solution;
[0046] Then, sodium hydroxide is added dropwise to the above silver nitrate solution until it becomes alkaline, mixed evenly, and allowed to stand to obtain a precipitate;
[0047] The precipitate is centrifuged, washed and dried to obtain silver oxide.
[0048] Furthermore, the concentration of the silver nitrate solution is 1 to 2 mol·L -1, the concentration of sodium hydroxide is 0.5~1mol·L -1 ; Add sodium hydroxide dropwise into the above silver nitrate solution until it becomes alkaline, pH = 9.
[0049] Furthermore, the mass ratio of the organic carbon source precursor to the silver-containing compound is (40-80):(60-100). Preferably, the organic carbon source precursor is polyvinyl pyrrolidone, and the silver-containing compound is silver oxide.
[0050] Furthermore, the grinding process specifically includes: placing the organic carbon source precursor and the silver-containing compound in an agate jar and ball milling for 8-12 hours.
[0051] Furthermore, the calcination process specifically includes: placing the solid mixture in a calcination device (such as a tubular furnace), heating it to 700-800° C. at 2-5° C. / min under an inert gas atmosphere, and maintaining it for 1-2 hours.
[0052] Furthermore, the washing and drying process specifically includes: washing the calcined product with water, and then drying it at a temperature of 60 to 80° C. The calcined product is washed with a large amount of deionized water, and then dried to obtain carbon-coated nanosilver particles; deionized water can be used for washing multiple times to make the washing more thorough.
[0053] The present invention also provides a carbon-coated nano-silver particle, which is prepared by the above-mentioned method for preparing the carbon-coated nano-silver particle.
[0054] The present invention also provides a conductive silver paste, which comprises:
[0055] Silver powder 82-88%;
[0056] 1-7% of the carbon-coated nanosilver particles as described above;
[0057] Glass powder 1-3%;
[0058] Organic resin 4-6%;
[0059] Organic solvent 2-8%;
[0060] Thixotropic agent 0.1~0.3%;
[0061] Leveling agent 0.2~0.5%;
[0062] Dispersant 0.1~0.3%.
[0063] Among them, the glass powder is mainly composed of Pb, B, Si, Ge, Zn and some alkali metal elements (such as one or more of Li, Na, K and Rb), and is prepared by processes such as high-temperature liquefaction, water quenching and grinding;
[0064] The organic solvent is one or more of diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, alcohol ester dodecaphosphate, dibutyl phthalate, polyamide wax, and acetyl tributyl citrate;
[0065] The organic resin is one or more of ethyl cellulose, polyvinyl butyral resin, SEBS resin, and cellulose acetate butyrate;
[0066] The thixotropic agent can be polyamide wax;
[0067] The dispersant may be a silicone ether;
[0068] Phosphate ester can be selected as the leveling agent.
[0069] Conductive silver paste includes the following preparation steps:
[0070] Preparation of an organic carrier (including an organic resin, an organic solvent, a thixotropic agent, a leveling agent and a dispersant): weighing the raw materials of the organic carrier according to a set ratio, heating and stirring to mix, high-speed centrifugation to disperse uniformly, and then filtering to obtain the organic carrier;
[0071] Preparation of carbon-coated silver nanoparticles:
[0072] Dissolve 170 g of AgNO3 in 500 ml of deionized water, stir continuously for 1 h in a dark environment, then drop 0.5 mol / L of NaOH into the mixture until the pH is close to 9, let stand until the reactant is completely precipitated, then centrifuge, wash and dry to obtain silver oxide;
[0073] 40 g of PVP (polyvinyl pyrrolidone) and 60 g of silver oxide were mixed, then placed in a ball mill for 12 hours, and then transferred to a tube furnace, heated to 700-800° C. at a heating rate of 2-5° C. / min under an inert gas atmosphere, and kept warm for 1 hour; the resulting calcined product was placed in a glass beaker, washed with a large amount of deionized water, and dried in an oven at 80° C. to obtain carbon-coated nanosilver particles.
[0074] The prepared silver powder, carbon-coated nanosilver particles and glass powder are added to the prepared organic carrier according to the mass ratio, mixed and stirred evenly, and then ground and filtered to obtain the required conductive silver paste.
[0075] Example 1
[0076] (1) Preparation of carbon-coated silver nanoparticles:
[0077] Dissolve 170 g of AgNO3 in 500 ml of deionized water, stir continuously for 1 h in a dark environment, then drop 0.5 mol / L of NaOH into the mixture until the pH is close to 9, let stand until the reactant is completely precipitated, then centrifuge, wash and dry to obtain silver oxide;
[0078] 40g of PVP (polyvinyl pyrrolidone) and 60g of silver oxide were mixed, then placed in a ball mill for 12 hours, and then transferred to a tube furnace, heated to 700-800°C at a heating rate of 2-5°C / min under an inert gas atmosphere, and kept warm for 1 hour; the resulting calcined product was placed in a glass beaker, washed with a large amount of deionized water, and dried in an oven at 80°C to obtain carbon-coated nanosilver particles; by scanning electron microscopy, the following was obtained: Figure 1 SEM images of carbon-coated silver nanoparticles are shown.
[0079] (1) Preparation of conductive silver paste:
[0080] The composition comprises the following components by mass percentage: 4% organic resin, 0.2% thixotropic agent, 0.2% leveling agent, 0.3% dispersant, 4.1% organic solvent, 2.2% glass powder, 88% micron-sized silver powder, and 1% carbon-coated nano-silver particles;
[0081] The organic resin includes: 50% SEPS resin, 30% ethyl cellulose resin, and 20% polyvinyl butyral resin;
[0082] The thixotropic agent is polyamide wax;
[0083] The dispersant is a silicone ether;
[0084] The leveling agent is phosphate ester;
[0085] The organic solvent is a mixture of diethylene glycol butyl ether acetate, alcohol ester dodecahydrate, diethylene glycol dibutyl ether, methyl phthalate and tripropylene glycol monomethyl ether.
[0086] The preparation steps of the conductive silver paste include: weighing the corresponding weight percentages of organic resin, thixotropic agent, leveling agent, dispersant, organic solvent, glass powder, micron-sized silver powder, and carbon-coated nano-silver particles according to the ratio, mixing and stirring the components evenly, then three-roll grinding, adjusting the viscosity, and finally filtering to obtain the desired conductive silver paste.
[0087] Example 2
[0088] The method for preparing carbon-coated nano-silver particles and conductive silver paste in Example 2 is the same as that in Example 1; the difference between Example 2 and Example 1 lies in the content of each component of the conductive silver paste; the conductive silver paste in Example 2 comprises the following components by mass percentage: 4% organic resin, 0.2% thixotropic agent, 0.2% leveling agent, 0.3% dispersant, 4.1% organic solvent, 2.2% glass powder, 86% micron-sized silver powder, and 3% carbon-coated nano-silver particles.
[0089] Example 3
[0090] The method for preparing carbon-coated nano-silver particles and conductive silver paste in Example 3 is the same as that in Example 1; the difference between Example 3 and Example 1 lies in the content of each component of the conductive silver paste; the conductive silver paste in Example 3 comprises the following components by mass percentage: 4% organic resin, 0.2% thixotropic agent, 0.2% leveling agent, 0.3% dispersant, 4.1% organic solvent, 2.2% glass powder, 84% micron-sized silver powder, and 5% carbon-coated nano-silver particles.
[0091] Example 4
[0092] The method for preparing carbon-coated nano-silver particles and conductive silver paste in Example 4 is the same as that in Example 1; the difference between Example 4 and Example 1 lies in the content of each component of the conductive silver paste; the conductive silver paste in Example 4 comprises the following components by mass percentage: 4% organic resin, 0.2% thixotropic agent, 0.2% leveling agent, 0.3% dispersant, 4.1% organic solvent, 2.2% glass powder, 82% micron-sized silver powder, and 7% carbon-coated nano-silver particles.
[0093] Comparative Example 1
[0094] The conductive silver paste includes the following components by mass percentage: 4% organic resin, 0.2% thixotropic agent, 0.2% leveling agent, 0.3% dispersant, 4.1% organic solvent, 2.2% glass powder, and 89% silver powder;
[0095] The organic resin includes: 50% SEPS resin, 30% ethyl cellulose resin, and 20% polyvinyl butyral resin;
[0096] The thixotropic agent is polyamide wax;
[0097] The dispersant is a silicone ether;
[0098] The leveling agent is phosphate ester;
[0099] The organic solvent is a mixture of diethylene glycol butyl ether acetate, alcohol ester dodecahydrate, diethylene glycol dibutyl ether, methyl phthalate and tripropylene glycol monomethyl ether.
[0100] The preparation steps of the conductive silver paste include: weighing the corresponding weight percentages of organic resin, thixotropic agent, leveling agent, dispersant, organic solvent, glass powder, and micron-sized silver powder according to a set ratio, mixing and stirring evenly, then three-roll grinding, then adjusting the viscosity, and finally filtering to obtain the desired conductive silver paste.
[0101] The conductive silver paste prepared in the above-mentioned Examples 1-4 and Comparative Example 1 was screen-printed on the battery cell, and then dried, sintered and cooled to obtain a battery containing printed silver grid line electrodes. The obtained battery was subjected to electrical performance testing. The electrical performance test results are shown in Table 1.
[0102] Table 1 Conductive silver paste test data table
[0103]
[0104] It can be seen from Table 1 that, compared with Example 1, when part of the silver powder is replaced by carbon-coated nano-silver particles in Examples 1-4, the conductive silver paste still has good electrical properties; it can be seen that part of the silver powder can be replaced by adding carbon-coated nano-silver particles, thereby reducing the overall cost of the paste, and the conductive silver paste can still maintain good conductivity, and the addition of carbon-coated nano-silver particles does not affect the overall performance of the conductive silver paste.
[0105] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to the technical contents disclosed above without departing from the scope of the technical solution of the present invention, which are equivalent embodiments of equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing carbon-coated nanosilver particles, characterized in that: The following steps are involved: mixing and grinding an organic carbon source precursor and a silver-containing compound; calcining the ground solid mixture under an inert gas atmosphere; The calcined product is cooled, washed and dried to obtain carbon-coated nano-silver particles.
2. The method for preparing carbon-coated nanosilver particles according to claim 1, characterized in that: The silver-containing compound is silver oxide or a silver salt which is decomposed to obtain silver element in the process of preparing the carbon-coated nano-silver particles.
3. The method for preparing carbon-coated nanosilver particles according to claim 2, characterized in that: The silver-containing compound is silver oxide, and the silver oxide is prepared by the following steps: dissolving silver nitrate in deionized water to obtain a silver nitrate solution; Then, sodium hydroxide is added dropwise to the above silver nitrate solution until it becomes alkaline, mixed evenly, and allowed to stand to obtain a precipitate; The precipitate is centrifuged, washed and dried to obtain silver oxide.
4. The method for preparing carbon-coated nanosilver particles according to claim 3, characterized in that: The concentration of silver nitrate solution is 1-2 mol·L -1 , the concentration of sodium hydroxide is 0.5~1mol·L -1 .
5. The method for preparing carbon-coated nanosilver particles according to claim 1, characterized in that: The mass ratio of the organic carbon source precursor to the silver-containing compound is (40-80):(60-100).
6. The method for preparing carbon-coated nanosilver particles according to claim 1, characterized in that: The grinding process specifically includes: placing the organic carbon source precursor and the silver-containing compound in an agate jar and ball milling for 8-12 hours.
7. The method for preparing carbon-coated nanosilver particles according to claim 1, characterized in that: The calcination process specifically includes: placing the solid mixture in a calcination device, heating it to 700-800° C. at a rate of 2-5° C. / min under an inert gas atmosphere, and maintaining it for 1-2 hours.
8. The method for preparing carbon-coated nanosilver particles according to claim 1, characterized in that: The cleaning and drying process specifically includes: washing the calcined product with water and then drying it at a temperature of 60 to 80°C.
9. A carbon-coated nanosilver particle, characterized in that: The carbon-coated nanosilver particles are prepared by the method for preparing the carbon-coated nanosilver particles according to any one of claims 1 to 8.
10. A conductive silver paste, characterized in that: Taking the total weight of the conductive silver paste as 100%, the conductive silver paste comprises: Silver powder 82-88%; 1-7% of the carbon-coated nanosilver particles as claimed in claim 9; Glass powder 1-3%; Organic resin 4-6%; Organic solvent 2-8%; Thixotropic agent 0.1~0.3%; Leveling agent 0.2~0.5%; Dispersant 0.1~0.3%.
Citation Information
Patent Citations
Preparation method of carbon-loaded nano-silver catalyst
CN110548507A